Predictors for outcomes of noninvasive, individualized transcranial magnetic neuromodulation in multiple sclerosis women with neurogenic voiding dysfunction - Jang, Yongchang; Tran, Khue; Shi, Zhaoyue; Christof, Karmonik; Choksi, Darshil; Salazar, Betsy H.; Lincoln, John A.; Khavari, Rose (Continence (Amsterdam), 2022)
Purpose: Multiple sclerosis (MS) is a multifocal demyelinating disease that affects the central nervous system (CNS) and commonly leads to neurogenic lower urinary tract dysfunction (NLUTD). Proper storage and release of urine relies on synchronized activity of the LUT, which is meticulously regulated by supraspinal circuits, making it vulnerable to diseases such as MS. NLUTD, characterized by voiding dysfunction (VD), storage issues, or a combination of both is a common occurrence in MS. Unfortunately, there are limited treatment options for NLUTD, making the search for alternative treatments such as transcranial rotating permanent magnet stimulation (TRPMS) of utmost importance. To assess effectiveness of treatment we also need to understand underlying factors that may affect outcomes, which we addressed here. Methods: Ten MS subjects with VD and median age of 54.5 years received daily TRPMS sessions for two weeks. Five pre-determined regions of interest (ROIs) known to be involved in the micturition cycle were modulated (stimulated or inhibited) using TRPMS. Clinical data (non-instrumented uroflow and urodynamics parameters, PVR, bladder symptom questionnaires) and neuro-imaging data were collected at baseline and following TRPMS via 7-Tesla Siemens MAGNETOM Terra magnetic resonance imaging (MRI) scanner. Each participant underwent functional MRI (fMRI) concurrently with a repeated urodynamic study (UDS). Baseline data of each arm was evaluated to determine any indicators of successful response to treatment. •Baseline clinical factors can serve as predictors of response to treatment in MS.•Distinctive supraspinal activation may be indicative of response to treatment.•Individualized brain neuromodulation can improve voiding dysfunction in MS.